Association Between Self-Reported Kinesiophobia and Single-Leg Hop for Distance in Patients With ACL Reconstruction: A Systematic Review. (September 2022) - Bakhsh, Hadeel R.; Metikala, Sreenivasulu; Billy, Gregory G.; Vairo, Giampietro L.
Context: Psychological readiness is a significant factor in determining successful return to sport (RTS) and physical activities after anterior cruciate ligament (ACL) reconstruction. Knowing the influence of kinesiophobia on physical tests that are used to guide RTS, such as the single-leg hop for distance (SLHD), would contribute to advancing clinical practice. Objective: To investigate the association between kinesiophobia and SLHD performance in patients after ACL reconstruction. Data Sources: A comprehensive search strategy entailed surveying 6 databases for relevant articles published from January 2009 to March 2021. Study Selection: Articles published in English that were a minimum of level 3 evidence describing kinesiophobia, as measured by the Tampa Scale for Kinesiophobia, and related to SLHD performance in patients after ACL reconstruction. Study Design: Systematic review. Level of Evidence: Level 3. Data Extraction: Study characteristics, sample population demographics, instrument(s), or approach(s) used to assess kinesiophobia and SLHD performance, and corresponding results. Results: A total of 152 potential studies were identified, 106 studies underwent screening, 40 were reviewed in full, and 7 studies were included. Meta-analysis could not be performed because of differences in experimental design among studies and instances of missing outcome data. Currently, moderate evidence indicates patients with ACL reconstruction that exhibit less kinesiophobia perform better on the SLHD test. Conclusion: The outcomes of this review propose that sports health practitioners consider the influence of kinesiophobia on SLHD performance as a criterion for RTS and physical activities in patients after ACL reconstruction. Higher quality studies are necessary to establish the extent of association between these variables.